Sex-related differential response to clomipramine treatment in a rat model of depression - Kokras, N; Antoniou, K; Dalla, C; Bekris, S; Xagoraris, M; Ovestreet, D H; Papadopoulou-Daifoti, Z. (J Psychopharmacol, 2009)
Research in affective disorders is often performed without considering sex differences, although women are predominantly affected. Consequently, the potential sex-dependent action of antidepressants remains elusive. We investigated whether Flinders sensitive line (FSL) of rats, a model of depression, would present sex-differentiated responses to antidepressant treatment. FSL and Sprague-Dawley rats were treated with clomipramine 10 mg/kg/day for 14 days. Subsequently, they were subjected to either a single session of the forced swim test or an estimation of serotonergic function in the prefrontal cortex, hippocampus, amygdala and hypothalamus. Male FSL displayed increased immobility duration, decreased active behaviours, increased serotonin tissue levels and a reduced serotonin turnover rate in most brain areas studied. Female FSL showed a distinct profile, consisting of decreased immobility latency, increased climbing duration, limited serotonergic deviations and no difference in the serotonin turnover rate in comparison with controls. Interestingly, despite baseline differences, clomipramine treatment reversed all relevant behavioural responses and increased the serotonin turnover rate in both sexes. However, the latter effect was remarkably more pronounced in females. It is concluded that, in this animal model of depression, chronic clomipramine treatment attenuated baseline sex differences in the phenotype while maintaining or intensifying the sex differentiation in the serotonergic endophenotype.
Keywords: Animals; Antidepressive Agents, Tricyclic/*therapeutic use; Clomipramine/*therapeutic use; Depression/*drug therapy/psychology; Disease Models, Animal; Female; Hydroxyindoleacetic Acid/analysis; Male; Rats; Rats, Sprague-Dawley; Serotonin/analysis/metabolism; Sex Characteristics; Swimming